Legal pluralism in the practice of informed consent among indigenous communities - RA. Sri Hardini; Agustinus Giri Respati; RM. Achmad Roeswandi; Imam Ropii (Institute of Computer Science (IOCS), 2026)
The transformation of individual autonomy standards in modern health law often creates a conflict of norms when implemented within the communal social structures of indigenous peoples. This research aims to analyze the dialectics of legal pluralism in the practice of medical informed consent to find a middle ground between centralistic state regulations and the